Strategi Pembelajaran Inkuiri dalam Pembentukan Karakter Mandiri pada Siswa Generasi Z di Madrasah Aliyah Swasta Babussalam Kecamatan Payaraman Kabupaten Ogan Ilir - Larissa Putri Isyara; Asri Karolina; Maryamah Maryamah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The purpose of this study is to analyze inquiry learning strategies in the formation of independent character of Generation Z in Madrasah Aliyah Private Babussalam Payaraman, and to analyze the implications of the application of these strategies on students' independent character. The research method used is a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model which included the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that first, the inquiry learning strategy is applied through five main stages, namely: (a) defining problems (b) localize and limit the problem (c) formulate a hypothesis, (d) evaluating data and (e) draw conclusions, namely compiling the findings independently and logically based on the critical thinking process. Second, this strategy has been proven to be able to form the independent character of generation Z, namely: independence in the learning process, responsibility for tasks, courage in making decisions, the ability to reflect on oneself, perseverance in facing challenges, the habit of seeking additional information, high curiosity, the ability to control oneself in using digital media, and ethics and social responsibility. Third, the implications of this study show that inquiry learning strategies play a significant role in the formation of the independent character of Generation Z.